The impact of multinational and domestic enterprises on regional productivity: evidence from the UK. Issue 2 (1st February 2019) - Bournakis, Ioannis; Papanastassiou, Marina; Pitelis, Christos
ABSTRACT: The paper explores the respective effects of multinational enterprises (MNEs) and domestic enterprises (DOMEs) on regional productivity in the case of UK regions. The empirical evidence shows that the more intensive in terms of research and development and intangibles, MNEs have a stronger effect on regional productivity than DOMEs. However, when one controls for the origin of the MNEs, it is found that DOMEs can outperform MNEs from certain countries. It is submitted that regions that lag behind can absorb the intangible assets of DOMEs more readily; and that MNE strategies may not be always aligned to the needs of host regions.